[Letter from Dan C. Alverson to TAN members regarding Los Angeles City Council ordinance restricting workplace smoking] - ALVERSON DC (Tufts Archival Research Center, 2007)
Missing Attachments; Letter from Dan C. Alverson to TAN members urging them to write letters to their councilmen in opposition of Los Angeles City Council ordinance restricting smoking in the office workplace. Accuses ordinance of being unfair, unwanted, and unnecessary. Provides numbers and adresses of council members and emphasizes immediate response.